How We Braid Our Lives Together with Our Ancestors - Lafferty, Anne (Ethnologies, 1998)
There is a range of different ways in which the traditions one has grown up with can be incorporated into what one does later. Neo-Pagan adults were generally raised in other religions, but they do not necessarily leave behind the traditions of their families of origin. Each of my informants incorporated some material from her family into her current beliefs and/or practices, but each also significantly modified or moved away from those traditions.